Synthetic Biology of Cyanobacteria (Advances in Experimental Medicine and Biology,, 2018)
This volume highlights recent breakthroughs in the interdisciplinary areas of synthetic biology, metabolic engineering and bioprocess engineering for the production of green chemicals. It also presents practical experimental and computational tools for the design, construction and manipulation of cyanobacteria cell factories. The respective contributions cover new technologies in the field, such as novel genetic transformation techniques and bioinformatics analysis methods and address various aspects of cyanobacterial synthetic biology, offering a valuable resource for students and researchers in the fields of industry microbiology and biomedical engineering.